Study on Plastic Coated Overburnt Brick Aggregate as an Alternative Material for Bituminous Road Construction - Dipankar Sarkar; Manish Pal; Ashoke K. Sarkar (Advances in Materials Science and Engineering)
There are different places in India where natural stone aggregates are not available for constructional work. Plastic coated OBBA can solve the problem of shortage of stone aggregate to some extent. The engineers are always encouraged to use locally available materials. The present investigation is carried out to evaluate the plastic coated OBBA as an alternative material for bituminous road construction. Shredded waste plastics are mixed with OBBA in different percentages as 0.38, 0.42, 0.46, 0.50, 0.54, and 0.60 of the weight of brick aggregates. Marshall Method of mix design is carried out to find the optimum bitumen content of such bituminous concrete mix prepared by plastic coated OBBA. Bulk density, Marshall Stability, flow, Marshall Quotient, ITS, TSR, stripping, fatigue life, and deformations have been determined accordingly. Marshall Stability value of 0.54 percent of plastic mix is comparatively higher than the other mixes except 0.60 percent of plastic mix. Test results are within the prescribed limit for 0.54 percent of plastic mix. There is a significant reduction in rutting characteristics of the same plastic mix. The fatigue life of the mix is also significantly higher. Thus plastic coated OBBA is found suitable in construction of bituminous concrete road.